Extensive venous thrombosis in a healthy young man with a short inferior vena cava syndrome treated successfully with rivaroxaban. (16th November 2012) - Khalafallah, Alhossain A; Renu, Shamsunnaher; Sharp, Colin; Hannan, Terry
Abstract : We report a case of an incidental finding of congenital absence of the intrahepatic segment of the inferior vena cava (IVC) complicated by extensive bilateral deep venous thrombosis (DVT) with significant oedema following a long-distance road trip. Initially the patient failed treatment with standard anticoagulation therapy with enoxaparin and warfarin. However, he has responded to the new oral antifactor-Xa anticoagulant (rivaroxaban). Within a few days, rivaroxaban improved the oedema and DVT. The significant features of this case are the unusual presentation, the poor response to initial standard anticoagulation therapy and the beneficial outcomes when managed with the novel new anticoagulant. The patient has continued the new treatment regularly for the last 12 months with good toleration and without side effects. This report presents the findings, management and outcomes in a case of extensive bilateral DVT in a previously healthy young man who was found to have a congenital short IVC.